TAMAN KOTA SEBAGAI SARANA REKREASI DAN PENINGKATAN KEBAHAGIAAN HIDUP (Studi kasus pada taman-taman tematik di kota Bandung) - Suherlan, Herlan; Pramesti, Bilkis (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2017)
This study aims to assess the suitability of urban parks in a region as a means of recreation that can accommodate user activities and meet the needs of public recreation. Currently the provision of leisure, recreation and tourism facilities is an indicator for the sustainability of urban development, so development in some urban areas now leads to city parks that provide space as a recreational facility that can improve the quality of life and make a city fit to be a place to live Which is convenient. The approach in this research is qualitative naturalistic approach. Data collection techniques used were interview, observation and documentation study. The object of research in the form of thematic parks in the city of Bandung. The results of the research show that (1) Bandung city park development has now lead to the use of the park as a recreational facility that offers a wide range of recreational opportunities both active and passive by optimizing its function in improving the index of happiness of the community; (2). The park in Bandung is in a strategic location with the city center and integrated with urban development; (3) Facilities to support recreational activities are not yet available optimally, there is no integration of various stakeholders in the development of the park as a means of recreation. Based on the results of the research concluded that the development of Bandung city park is currently not suitable for use as a means of public recreation. Recommendation from the above conclusion is the importance of integration conducted by related institutions in the organization and management of the park to serve as a means of public recreation in the city of Bandung.